Assembling export markets : the making and unmaking of global food connections in West Africa - Ouma, Stefan (Chichester, West Sussex, UK ; Malden, MA : John Wiley & Sons Inc., 2015)
"Assembling Export Markets explores the origins of global agrifood chains through an examination of the new frontier regions of the global fresh produce market that has emerged in the West African Republic of Ghana over the past decade"--
Powerful ValorimetersPricing, Returns, and Visible hands; Power Relations as Relations of Accounting; Accounting: Frontstage; Accounting: Backstage; Conclusion; Endnotes; Chapter 8 Market Crises: When Things Fall Apart, or Won't Come Together; A Model in Crisis; MD2 Takes Over the Market, or How Goods Become Delegitimated; Trading Down in Times of Crisis; Currency and Capital Volatilities; When the Supply Base Disenrolls ...; Reassembling the Market Social?; Recalcitrant "Nature" and the Crisis of the Developmental Market
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Produce trade -- Social aspects -- Ghana; Farm produce -- Ghana -- Marketing; Agriculture -- Economic aspects -- Ghana; SOCIAL SCIENCE / Human Geography; Agriculture -- Economic aspects -- Ghana; Farm produce -- Ghana -- Marketing; Ghana -- Commerce; Ghana -- Economic conditions; Produce trade -- Social aspects -- Ghana; Ghana -- Commerce; Ghana -- Economic conditions; Electronic books; Electronic books